Exercise - Exploring Mutuality and Discordance(s) Between Sport and Public Health - Eling D. de Bruin (MDPI AG, 2013)
Sports is a peer-reviewed scientific journal that revolves around the interdisciplinary area of exercise sciences applied in sport and public health. The intention of Sports is to link several scientific disciplines in an integrated fashion in order to address critical issues related to exercise science, sports and public health. As the first Editor-in-Chief of Sports, I would like to share a few comments about this interdisciplinary field of research by discussing the mutuality and discordances between exercise as it is applied in sports and public health.